Survival, consumption and reproduction of Amblyseius longispinosus (Evans) (Acari Phytoseiidae) on various food items and its comparative biology on two species of spider mites - De Leon-Facundo, Josephine B.; Corpuz-Raros, Leonila A. (2005)
To evaluate the possibility of using a cheap prey alternative for mass rearing Amblyseius longispinosus (Evans), the survival, consumption and reproduction on eggs of different animal prey were evaluated singly or in combination with castor pollen as food supplement. The predator failed to develop and reproduce normally when fed with factitious prey acaroids, Suidasia pontifica Oudemans and Tyrophagus putrescentiae (Schrank). Only the natural prey spider mites, Tetranychus truncatus Ehara and T. kanzawai (Kishida), were suitable for the predator. Addition of castor pollen to either natural or factitious prey did not significantly improve rate of development and survival of immature stages, and oviposition of adults. To determine the better spider mite for mass rearing, the biology of the predator on the two natural prey species was compared. Development and reproduction of A. longispinosus fed with the two spider mites were comparable. However, the predator required significantly fewer prey eggs to produce an egg when fed with T. truncatus whose eggs are slightly but not significantly larger than those of T. kanzawai. The present findings indicate that both spider mites are suitable as prey for mass rearing A. longispinosus.
Keywords: Acaricides; Survival; Food consumption research; Biological pest control agents